2004
DOI: 10.1097/00002826-200405000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B, Neurotensin, and Cannabinoid Receptor Antagonists and Parkinson Disease

Abstract: The neuropeptides neurokinin B, neurotensin, and anandamide, the endogenous ligands of NK3, NT1, and CB1 receptors respectively, are known to interact with brain dopaminergic transmission. This study evaluated the effects of these three antagonists of the NK3 (SR 142801), neurotensin (SR 48692), and cannabinoid (SR 141716) receptors on the severity of motor symptoms and levodopa-induced dyskinesias after administration of a single dose of levodopa in 24 patients with Parkinson disease. In this exploratory rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
85
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 9 publications
0
85
0
2
Order By: Relevance
“…Notwithstanding the above, studies using SR141716 in rat and primate models of PD or LID (Meschler et al, 2001;van der Stelt et al, 2005) provided conflicting results. Rimonabant treatment also failed to influence dyskinesia in the first small-scale, randomized, double-blind, placebo-controlled human study (Mesnage et al, 2004). However, the dose used in this human study was approximately 10-fold lower (0.3 mg/kg versus.…”
mentioning
confidence: 79%
“…Notwithstanding the above, studies using SR141716 in rat and primate models of PD or LID (Meschler et al, 2001;van der Stelt et al, 2005) provided conflicting results. Rimonabant treatment also failed to influence dyskinesia in the first small-scale, randomized, double-blind, placebo-controlled human study (Mesnage et al, 2004). However, the dose used in this human study was approximately 10-fold lower (0.3 mg/kg versus.…”
mentioning
confidence: 79%
“…Finally, an open-Blabel^study of smoked marijuana in 22 Israeli patients showed improvement in the number of dyskinesias observed after dopa challenge, 30 min after smoking the cigarette [19]. In an interesting twist, a single dose of the CB 1 R antagonist rimonabant (SR141716) was found to have no effect on motor symptoms, or induced dyskinesias in 8 patients [20].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 95%
“…Lastly, clinical studies with cannabinoids in patients with PD are still limited, with most of them addressing only the relief of specific symptoms, for example bradykinesia [123], tremor [124], and levodopa-induced dyskinesia [125]. No clinical data exist in relation to the neuroprotective effects of cannabinoids.…”
Section: Cannabinoids and Chronic Neurodegenerative Disorders: II Pdmentioning
confidence: 99%